BARRIERS AND FACILITATORS OF THE APPLICATION OF THE AIR STACKING TECHNIQUE IN PATIENTS WITH NEUROMUSCULAR DISEASES: A LITERATURE REVIEW (CIPEEX, 2025)
Introduction: Neuromuscular diseases (NMD) cause progressive and irreversible damage to the peripheral neuromuscular system, weakening skeletal, cardiac, and respiratory muscles. This leads to difficulties in locomotion, swallowing, and, in severe cases, death from respiratory failure. Coughing is crucial for protecting the airways, but it becomes ineffective in patients with NMD, increasing the risk of respiratory infections. Cough assistance techniques with insufflation and air stacking, using a manual resuscitator or mechanical ventilator, are effective for removing secretions and improving lung function. Objective: To review the literature in order to analyze the barriers and facilitators of air stacking techniques to improve the quality of life of patients with NMD. Methodology: Articles in English and Portuguese from Pubmed, Google Scholar, and Scielo were included. Results: The study confirmed that the technique is beneficial for patients with DMD, and the knowledge gained can be applied to these patients. However, a limitation of the study is that the data analyzed were only for the short-term benefits of the techniques, and further research is needed to evaluate the long-term effects of these maneuvers in people with neuromuscular diseases. Conclusion: Based on the results of the articles selected to answer the initial clinical question, it can be concluded that the air stacking technique is effective for patients with neuromuscular diseases seeking to increase peak cough flow (PCF).
Keywords: Neuromuscular; Air Stacking; Barriers; Facilitators